Hexavalent Chromium Removal from Electroplating Waste Using Biochitin from L.Vanamme Shrimp Shell Waste - Angelina Rosmawati; Barlah Rumhayati; Arie Srihardyastutie (Chemistry Department, The University of Brawijaya, 2020)
The increasing number of electroplating industries in this globalization era has a negative impact on the environment because of its liquid waste containing high concentrations of hexavalent chromium, Cr (VI). To overcome this problem, biochitin extracted from white shrimp shell waste (L.vanamme) has been used to adsorb Cr (VI) from electroplating waste. Biochitins were extracted through single and sequential fermentation method using L.plantarum and B.thuringiensis bacteria. The optimization process of Cr (VI) removal was done by using biochitin from different methods, at various mass of biochitin, the time of adsorption, and Cr (VI) concentration. Results showed that biochitin produced from the sequential fermentation method could optimally adsorb Cr (VI). By using 2 g of biochitin, Cr (VI) could be removed as much as 51.99 ± 0.41% during 6 hours. At the optimum condition, the selected adsorbent could remove Cr (VI) in the concentration range of 9.38 to 92.39 mg/L, which showed the adsorption capacity of 0.915 mg/g. The capability of biochitin for Cr (VI) removal was reinforced by the SEM EDS images, which show the presence of chromium compounds in the biochitin.